(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to identify the degree of using social networking sites by the basic stage English language teachers in the South Hebron Directorate during the Corona Pandemic. This study was conducted on a simple random sample of (150) male and female of primary school English language teachers in the Directorate of Education in South Hebron. The researcher used the descriptive approach, where the tool of the study was used after verifying their validity and stability. The results of the study indicate the overall degree of using social networking sites by the basic stage of English language teachers was significant. They also indicate that teachers mostly depended on the social networking sites (WhatsApp and Facebook) in distance learning during Corona pandemic. However, the existence of differences in the using of social networking sites by the basic stage of English language teachers to the variable of gender, the benefit of males, for the variable of academic qualification, in favor of a Master and higher, for the variable of specialization, and for the specialization of English Methods. Based on the previous finding, the researcher recommends training the teachers and the students on using social networking sites and mixing them in learning process, while diversifying the social network platforms which used and not being one platform, as well as benefiting from local and international experiences in employing social networking in learning process, especially distance learning.